Managing Schools with Instructional Leadership: Headteachers’ Perspective, Practice and Problem in Nuwakot District - Sadaula, Purna Bahadur; Thapa, Dharma Jung (The Journal of Nuwakot Adarsha Multiple Campus, 2025)
The growing international literature on instructional leadership (IL) shows that its practice changes with cultural and local factors. Previous studies have shown that while head teachers (HTs) in Nepal's community schools are expected to lead teaching and learning, they often focus on administrative tasks instead of key IL parts like teacher development, goal setting, curriculum guidance, and classroom checks. This study used qualitative methods, including interviews with 12 head teachers and observations in Nuwakot district, to find and understand the main barriers stopping IL in rural basic schools. Factors such as no clear recruitment policy, teacher shortages, lack of resources, political interference, low community support, and heavy workload are key problems affecting IL practice and success in Nepal. The findings help understand IL better in different local settings.